Caracterização do acidente de trânsito e gravidade do trauma: um estudo em vítimas de um hospital de emergência de Natal - Ramos, Cristiane da Silva (2008)
Descriptive exploratory study, with quantitative approach and prospective data performed on the Monsenhor Walfredo Gurgel Hospital Complex (MWGH), in Natal/RN, aiming to classify the type of motor vehicle involved in the accident, the public roadway s user quality and the more frequent injuries; to evaluate the severity of trauma in traffic accident victims; characterized the severity of the injuries and the trauma, and the type of motor vehicle involved. The population comprises 605 traffic accident victims, with data collected between October and December 2007. We used as a support for the evaluation of severity of injuries and trauma the Glasgow Coma Scale (GCSl), the Condensed Abbreviated Injury Scale (CAIS) and the Injury Severity Score (ISS). The results show that 82.8% of the victims were male; 78.4% were aged 18 to 38; the victims originating from the State s Countryside prevailed (43.1%); 24.3% of the population had completed middle-level instruction; 23.1% worked on commerce and auxiliary activities; most (79.4%) was catholic; 48.8% were married/consensual union; 76.2% earned up to two monthly minimum wages; Sunday was the day with the most accidents (25.1%); 47.4% were attended to in under an hour after the event; the motorcycle on its own was responsible for 53.2% of the accidents; 42.3% were attended to by the SAMU; 61.8% were victims of crashes; over half (53.4%) used individual protection equipment (IPE); 49.4% were helmets and 4.0% the seatbelt; 61.3% were motorcycle drivers; 43.3% of the accidents took place in the afternoon shift; from 395 drivers, 55.2% were licensed, and 50.7% among those had been licensed for 1 to 5 years; 90.7% of the victims had GCS1 between 13 and 15 points at the time of evaluation; the body area most affected was the external surface (35.9%); 38.8% of the injuries were light or moderate (AIS=1 and AIS=2); 83.2% had light trauma (ISS between 1 and 15 points). In face of the results, we can conclude that there is a risk for the elevation of injury severity and trauma resulting from traffic accidents, when these events are related to certain variables such as gender, age, weekday, the interval between the accident and the first care, ingestion of drugs, type of accident, the public roadway s user quality, the use of IPE, day shift, body regions and the type of motor vehicle involved in the accident